144: How do we Treat Acute Immune Thrombocytopoenia (ITP) in the Maritime Provinces?. Issue 6 (1st June 2014) - Lee, J; Crooks, B
Abstract: BACKGROUND: The diagnosis and management of immune thrombocytopoenia (ITP) of childhood is controversial amongst paediatricians. ITP is the most common bleeding disorder of childhood and is characterized by an isolated low platelet count (<100×10 9 /L). The disorder is usually self-limiting – nearly 80% of childhood ITP spontaneously resolve within a year. However, many patients receive therapy to avoid the rare incidence of clinically significant bleeding. Published guidelines have differed in recommendations for diagnosis and management. OBJECTIVES: This study aimed to explore approaches in managing acute ITP at the IWK Health Centre and across the Maritimes Provinces. DESIGN/METHODS: A literature review, retrospective chart review of ITP patients followed at the IWK since January 1, 1990, and an online survey of paediatricians' practices were conducted. RESULTS: Published guidelines are converging and encourage paediatricians to treat based on symptoms not absolute platelet counts. Chart review showed that 99 of 144 patients received at least one course of treatment – 60 of 99 with IVIg and 37 of 99 with corticosteroids. The decision to treat 66 of 99 was on platelet count alone. Bone marrow examinations, recommended in an atypical presentation or prolonged course of disease, were performed in 54 patients. IWK paediatricians relied on clinical experience in 135 cases and consultation with colleagues in 36 cases. Twenty-four Maritime paediatricians who responded to our online questionnaire manage ITP. 17completed the survey. Nineteen of 24 were uncertain of recommended diagnostic platelet counts for ITP. Two of 24 reported using published resources to complete the survey. Thirteen of 21 paediatricians reported they would use published guidelines to guide management in provided case scenarios and 17 of 21 would consult colleagues. CONCLUSIONS: Actual management of acute ITP differs from published guidelines: patients are treated more for platelet counts and may be over-investigated and over-treated. Lack of adequate documentation may bias results. Maritime paediatricians prefer managing patients collaboratively, suggesting that further education would benefit practice. A prospective pan-Canada survey would explore this further.